The effects of copper ions on the synthesis of periplasmic and membrane proteins in Acidithiobaeillus ferrooxidans as analyzed by SDS-PAGE and 2D-PAGE - Felicio, A. P.; Garcia, O.; Bertolini, Maria Celia [UNESP]; Ottoboni, LMM; Novo, MTM (Elsevier B.V., 2003)
The effects of 200 mM copper ions on the synthesis of membrane and periplasmic proteins were investigated in iron-grown cells of Acidithiobacillus ferrooxidans (At. ferrooxidans). Total membrane protein profiles of cells grown in the absence of copper ions (unadapted cells) and in the presence of copper ions (copper-adapted cells) were compared by two-dimensional polyacrylamide gel electrophoresis (2D-PAGE). Crude preparations of outer membrane and periplasmic proteins were analyzed by SDS-PAGE. The synthesis of proteins was diminished or increased in the presence of copper ions. Low molecular weight proteins (< 14 kDa) were significantly repressed by copper. These proteins are probably acidic proteins located in the outer membrane. An over-expression of a periplasmic protein of about 17 kDa was detected in the copper-adapted cells and was assumed to be rusticyanin, a 16.5-kDa periplasmic copper protein present in At. ferrooxidans cells and involved in the electron-transport chain of the iron oxidation pathway. To our knowledge, this is the first report of a possible involvement of the rusticyanin and outer membrane proteins in the mechanism of copper resistance in At. ferrooxidans. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: copper resistance; outer membrane protein; periplasmic protein; Acidithiobacillus ferrooxidans; 2D-PAGE; metal resistance; rusticyanin